Tax, Bonus Mechanism, Tunneling Incentive, Debt Covenant and Transfer Pricing in Multinational Companies - Sujana, I Ketut; Suardikha, I Made Sadha; Saraswati, Gusti Ayu Rai Surya (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
This research is aimed to test the influence of tax, bonus mechanism, tunneling incentive and debt covenant to transfer pricing of multinational companies. The seconder data used in this research is obtained by accessing  www.idx.co.id . The population of this research is a manufacture company registered in Bursa Efek Indonesia (Indonesia Stock Exchange) in year of 2012-2016. The sample taking technique used is purposive sampling. The number of sample in this research is 125 observations. The data collecting method used in this research is non-participant observation method and the data analysis technique used is logistic regression. The result is tunneling incentive has a positive influence to company decision in doing the transfer pricing. Meanwhile, tax, bonus mechanism, and debt covenant do not have influence to multinational company decision in doing the transfer pricing. Keywords : tax, bonus mechanism, tunneling incentive, debt covenant, transfer pricing.